Intervensi pada perilaku bidan tentang pelaksanaan inisiasi menyusu dini dengan menggunakan layanan pesan singkat - Widya Lionita; Ova Emilia; Trisasi Lestari (Fakultas Kedokteran Universitas Gadjah Mada, 2017)
Intervention on midwife behavior about early initiation of breastfeeding practice using short message servicePurposeThis research examined the effects of an intervention by delivering short message service towards midwife behavior.MethodsThis research was a quasi-experimental study with pre and post test design using control group. A total of 64 midwives in Palembang participated until data extraction. About 18 themes of short messages were delivered through participants’ mobile phone. Data were analyzed by univariate, bivariate, and linear regression tests.ResultsResults showed that the intervention improved early breastfeeding perceptions by about 7.3% (p= 0.0308). Participants’ knowledge was increased after intervention although there was no significant mean difference between groups. Almost all participants (over 80%) practiced imperfect early breastfeeding, especially in giving information since antenatal care, short-duration, and directing baby for sucking mother’s nipple.ConclusionNot all of participants facilitated early breastfeeding in every birth because of other factors such as unsupported mother and infant’s condition. Early initiation of breastfeeding is not easily implemented by health staff. It is better that midwives could motivate mothers to breastfeed within 1 hour since antenatal care. The important keys are having high commitment and confidence which contribute to midwives’ belief for practicing every step in every birth. We concluded that this research should be continued for long-term-analysis to give more significant results.